Fatores associados ao apoio social percebido por jovens e o desfecho sorológico para o HIV - Santos, Jamira Martins dos (2022)
Introduction: Over time, significant advances have been observed in the knowledge, prevention and treatment of HIV. Youth is considered to be a time of vulnerability enabling the adoption of risky behaviors. Social support plays an important role in preventing these behaviors. Objective: To analyze factors associated with social support perceived by young people and its influence on serological outcome for HIV infection. Method: Cross-sectional study, survey type, carried out at the Center for Testing and Counseling in the city of Campina Grande, Paraiba. The sample consisted of 101 young people, aged 15 to 24 years, recruited from the attendance to the service for rapid testing for HIV. For data collection, a validated instrument was used, containing sociodemographic and socio-structural variables and the social support scale Medical Outcome Study Social Support Survey (MOS-SSS) that addresses dimensions of affective, material, emotional/informational social support and positive social interaction. Data were analyzed using descriptive statistics and association by chi-square and Fisher's exact test. Perceived social support was classified as satisfactory (SSA) or unsatisfactory (ASI), being defined as ASI scores in the MOS-SSS below the 25th percentile of the total sample. The research was approved by the Ethics Committee under opinion no. 3,935,713. Results: The prevalence of seropositive observed in this group of young people was 6.9%. There was a higher proportion of HIV-positive tests among young men aged 20 to 24 years and homosexuals. There was an association between positive HIV serology, "homosexuals", "living parents" and "sexual orientation discrimination". In the overall analysis of the social support scale, 26 (26.75%) youth rated social support as unsatisfactory (MOS-SSS < 25th percentile). There was no statistically significant association between MOS-SSS dimensions and serological outcome. However, differences were found between sociodemographic/socio-structural variables and dimensions of social support. There was significance between the variables "sexual orientation" with affective social support (p<0.001), "living with" in relation to material support (p<0.002), and "sexual orientation discrimination", which showed significance with the dimension’s material support (p<0.034) and affective support (p<0.039). Conclusion: Knowing the factors associated with the social support perceived by young people, especially in conditions where social support is unsatisfactory, can strengthen the role of health teams as a source of social support and favor the development of actions to promote health and prevent HIV.